Analysis Of Apal Cue Time, Queue Length, And Delay Using Pkji 2023 - Irfan, Muhammad; Setyo Wibi, Gannang; Almodad Alle, Andri; Sutrisno, Widarto; Langit Gutama, Detha Sekar (Winter Journal: IMWI Student Research Journal, 2023)
The intersection of Kyai Haji Wahid Hasyim and Mataram Sewer Inspection Road, Dabag, Condongcatur, Depok District, Seman Regency, Yogyakarta. Initial observations show that the intersection is often congested due to heavy traffic flow, especially during peak hours. Congestion in the city of Yogyakarta, especially the sleman district, is unavoidable, especially at intersection points both on protocol roads and on small roads. This congestion can result in losses for road users such as reduced vehicle speed, increased waiting time, increased vehicle queues, and decreased environmental quality. to reduce this congestion, researchers analyzed the time of the apill signal, queue length, and delay so that the congestion could be resolved. Determine the right alternative to solve the problems contained in the intersection. Primary data collection was carried out in the field for seven days with peak hours in the morning at 07.00-08.00 WIB and in the afternoon at 16.30-17.30 WIB using CCTV as a traffic volume data counter. Traffic light signal data is obtained in the field by counting each approach. Secondary data used is obtained from the Population-related Service Agency such as the Central Bureau of Statistics. The data obtained is then analyzed using the Indonesian Road Capacity Guidelines 2023 (PKJI 2023) Signalized Intersection method. The highest capacity analysis results on October 02, 2023 with a vehicle volume of 2539 kend / hour. With the result time of all red time north direction 1 second, south direction 1.09 seconds, east direction 0.43 seconds, west direction 0.42 seconds. and green time lost a total of 17 seconds. Queue length in the north direction 160.19m, in the south direction 186.96m, in the east direction 54.48m, in the west direction 115.3m. Delay in the north direction 71.45 seconds. In the south direction 72.4 seconds, in the east direction 59.56 seconds, in the west direction 60.66 seconds.